2014
DOI: 10.1620/tjem.233.123
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Retained Interferon-Gamma Responsiveness in Individuals with a History of Pulmonary Tuberculosis

Abstract: The interferon gamma (IFN-γ) release assays (IGRAs) are the best method of detecting Mycobacterium tuberculosis infection. However, reports on IGRAs results obtained during and right after the treatment of tuberculosis (TB) have presented differing results. Some studies have shown declining responses, whereas other reports described persistent, fluctuating, or increasing responses. We postulated that the IGRA-positivity will decrease or revert long time after treatment of TB, and thus, evaluated the response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…Like others, we found that a previous history of TB treatment was associated with Mtb infection [7] and with TB disease [6,14,[16][17][18][19][20][21]. A positive IGRA test could [22] and even decades after completing treatment of active TB disease [23]. We observed the highest prevalence of Mtb infection in HHCs 25-49 years of age, with a pattern similar to early TST surveys [24,25] and a 2002 report from The Gambia [11] of increasing prevalence with age and declines in older adults.…”
Section: Discussionsupporting
confidence: 80%
“…Like others, we found that a previous history of TB treatment was associated with Mtb infection [7] and with TB disease [6,14,[16][17][18][19][20][21]. A positive IGRA test could [22] and even decades after completing treatment of active TB disease [23]. We observed the highest prevalence of Mtb infection in HHCs 25-49 years of age, with a pattern similar to early TST surveys [24,25] and a 2002 report from The Gambia [11] of increasing prevalence with age and declines in older adults.…”
Section: Discussionsupporting
confidence: 80%
“…Mtb -specific CD4 + T-cell responses are elevated during active TB, and a proportion of these cells can persist as memory cells after successful treatment ( 35 , 36 ). It has been estimated that ~70% of people cured of pulmonary TB exhibit positive tuberculin reaction and IGRA up to 30 years after treatment ( 37 ). With Mtb reinfection, these hosts are more likely to mount hyperactive CD4 + T-cell responses, leading to active TB.…”
Section: Protective Versus Pathological Immunity During Mtb Infectionmentioning
confidence: 99%
“…Similarly, biological or assay variability are commonly suggested as reasons for IGRA reversion [ 49 , 75 , 76 ]. Some emphasise that the “majority” with immunoreactivity “remain” positive [ 77 , 78 ]; cite studies from high-incidence settings and/or in strong reactors and report that reversion occurs infrequently [ 79 , 80 ]; or draw attention to the “stability” of negative responses, rather than the more dynamic positive responses [ 47 ]. Lastly, reversion that is observed to occur soon after presumed infection has been labelled “transient conversion” [ 81 , 82 ], giving the impression it is a phenomenon that exclusively occurs soon after exposure.…”
Section: Reversion Has Been Overlooked Dismissed and Downplayedmentioning
confidence: 99%